MAKNA WALI DAN AULIYĀ’ DALAM AL-QUR’AN (Suatu Kajian dengan Pendekatan Semantik Toshihiko Izutsu) - Ismatilah Ismatilah; Ahmad Faqih Hasyim; M. Maimun (UIN Siber Syekh Nurjati Cirebon, 2016)
In Indonesia context, the term wali and Auliya 'only have two meanings, those are wali as parents and wali as the close one with Allah and has peculiarity that other people do not have or wali is defined according to tasawuf, such as wali songo. However, in the holy Qur'an the word wali and auliya have different meaning depend on the relation of sintagmatik that is used in a word. So that, the researcher analyze the meaaning wali and Auliya.The formulation of this research are 1) how is the meaning of wali and Auliya 'in the holy Qurâ€™an? And 2) how is the basic meaning and word relational meaning of wali and Auliya 'in the holy Qur'an?The purpose of the research are: 1) to know the meaning of wali and Auliya in the holy Qur'an and 2) to know the basic meaning and relational word meaning of wali and Auliya'.This research is qualitative and what kind of research is a library to discuss the book, both in primary and secondary books that explain the semantic word guardian and Auliya 'in the Qur'an. The approach of this research is the semantic approach offered Toshihiko Izutsu. steps in the research is to determine the word that will be studied the meaning and concepts contained in it, tracing the roots of the word, transformation, and change the meaning, outlining categories of semantic guardian and Auliya 'according to the condition of the wearer, and compose semantic field to obtain an illustration or picture clearer about the meaning of a word.The results of this study is the first meaning of the word meaning guardian pick up close. The second is based on relational meaning, in the Qur'an the word guardian and Saints have various meanings of which are helper, protector, friend, leader, ruler, children, heirs, lover, coreligionists, and the close is righteous. In the development of meaning, the word guardian at the time of the Pre-Qur'anic means master, people who have power over something. At the time of Qur'anic word guardian and Saints have meaning as disbutkan above.The meaning of the word guardian and Auliya 'in the post-Qur'anic evolving in the context Indonesiaan is the first guardian of Sufi pandangn corner meaningful person who received special protection. because obedience to God. God has the absolute right to choose his servant to be a trustee. Both from the standpoint of jurisprudence family, guardian meaningful words the person who has the authority to perform a contract, guardian of marriage. Third from a social standpoint in meaningful parent / father or mother and meaningful leaders, such as mayors.Â Key words: wali, auliyÄâ€™, semantic, Qurâ€™an.